The lexical processing of Japanese collocations by Chinese Japanese-as-a-Foreign-Language learners: An experimental study by manipulating the presentation modality, semantic transparency, and translational congruency - Song, Qichao; Fei, Xiaodong; Matsumi, Norio (Frontiers in Psychology, 2023)
This study examined the processing of Japanese collocations by Chinese Japanese-as-a-Foreign-Language (JFL) learners. In the experiments, the presentation modality, semantic transparency, and translational congruency were manipulated during a lexical judgment task. Data analysis using linear mixed-effects models revealed the following. 1) In both conditions of semantic transparency and translational congruency, the auditory presentation was associated with longer reaction times than the visual presentation. 2) In the visual presentation condition, neither semantic transparency nor translational congruency showed significant effects. 3) In the auditory presentation condition, the reaction time for collocations with high semantic transparency tended to be longer than that for collocations with medium semantic transparency and significantly longer than that for collocations with low semantic transparency. The reaction time for collocations with congruent translation was longer than that for collocations with incongruent translation. These results support the dual-route model of Japanese collocational processing by Chinese JFL learners, which differs from the collocational processing of phonographic languages such as English and German. It became clear that whether the analytic or holistic processing dominates is closely related to the learners’ knowledge of Chinese and Japanese Kanji words and was strongly influenced by the presentation modality, semantic transparency, and translational congruency.